Coaches' Beliefs and Knowledge: Training Programs Used by French Professional Coaches to Increase Ball-Throwing Velocity in Elite Handball Players - Debanne, T.; Laffaye, G. (International Journal of Sports Science and Coaching, 2013)
The goal of this study is to understand through a questionnaire survey how professional French handball coaches build their training programs (TP) to increase ball velocity. Nineteen surveys (representing 67.86% of all coaches in the country) were received and then analyzed. The questionnaire was composed of three parts: coach characteristics; general strength; and handball-specific strength program for upper limbs and trunk. The questions were formulated for an analog Likert scale from 1 (strongly disagree; never; very low) to 6 (strongly agree; very often, very high). The results show that i) coaches preferentially use concentric and plyometric muscle contractions in order to increase player power and velocity output; ii) to increase ball velocity, coaches focus on shoulder internal rotation, elbow extension and abdominal oblique muscles; and iii) there is a difference of choice in the TP based on the coaches' level of academic degree (AD) and age: young coaches with high AD build their TP more in accordance with recent scientific knowledge, while older ones with low AD build TP based on either older knowledge or on beliefs.